2007
DOI: 10.1111/j.1399-3038.2007.00549.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of long‐term sublingual immunotherapy as an adjunct to pharmacotherapy in house dust mite‐allergic children with asthma

Abstract: Although sublingual immunotherapy (SLIT) is accepted to be a viable alternative of specific-allergen immunotherapy, the efficacy of long-term SLIT in asthmatic children is not well established. The efficacy of 3 yr of SLIT in addition to pharmacotherapy was compared with pharmacotherapy alone in a prospective, open, parallel-group, controlled study. Children with asthma aged 4-16 yr, sensitive to house dust mite (HDM) were followed up for a run-in period of 1 yr and then grouped as those who would receive SLIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 27 publications
4
49
0
3
Order By: Relevance
“…Sublingual immunotherapy (SLIT) appears to be associated with a lower incidence of systemic reactions and in a long-term treatment as an adjunct to pharmacotherapy results in the reduction of both the duration and the dose of inhaled corticosteroids and successful discontinuation along with an improvement of lung functions [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Sublingual immunotherapy (SLIT) appears to be associated with a lower incidence of systemic reactions and in a long-term treatment as an adjunct to pharmacotherapy results in the reduction of both the duration and the dose of inhaled corticosteroids and successful discontinuation along with an improvement of lung functions [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Высокая эффективность АСИТ, проводимой неинва-зивным сублингвальным методом, меньшая травматич-ность по сравнению с парентеральной иммунотерапией позволяют рекомендовать ее при аллергических заболе-ваниях у детей, особенно младшего возраста [14,17].…”
Section: результаты и обсуждениеunclassified
“…В нескольких других исследованиях среди детей дошколь-ного возраста также была подтверждена безопасность проведения сублингвальной АСИТ [17]. При анализе нежелательных явлений установлено, что у детей всех исследуемых групп они проявлялись на высоких дозах вводимых аллергенов и при нарушении диеты в течение курса иммунотерапии (употребление пищевых аллергенов, имеющих общие антигены с пыль-цой -орехи, яблоки, киви и т.д.…”
Section: результаты и обсуждениеunclassified
“…Double-blind, placebo-controlled studies have shown the efficacy and the safety of SLIT both in allergic rhinoconjunctivitis and asthma (16)(17)(18)(19)(20). Ultra-rush regimens of SLIT induction have been carried out with good safety and efficacy profiles (21)(22).…”
mentioning
confidence: 99%